Designed synthesis of MOF-derived magnetic nanoporous carbon materials for selective enrichment of glycans for glycomics analysis1. Issue 15 (21st April 2015) - Sun, Nianrong; Zhang, Xiangmin; Deng, Chunhui
<x xml:space="preserve">Abstract</x> In this work, magnetic nanoporous carbon (NPC) materials were synthesized by choosing a MOF as a sacrificial template and a carbon precursor, and applied to glycomics analysis by enriching N-linked glycans in bio-samples with high selectivity and efficiency.